2008
DOI: 10.1139/y08-032
|View full text |Cite
|
Sign up to set email alerts
|

Additional lack of iNOS attenuates diastolic dysfunction in aged ET-1 transgenic miceThis article is one of a selection of papers published in the special issue (part 1 of 2) on Forefronts in Endothelin.

Abstract: Endothelin-1 (ET-1) exhibits potent proinflammatory and profibrotic properties. Moreover, inflammation is a potent stimulus for inducible NO synthase (iNOS), which has been shown to contribute to cardiac injury. We thus hypothesized that ET-1-induced cardiac injury is attenuated by concomitant lack of iNOS. We established crossbred animals of ET-1 transgenic mice (ET+/+) and iNOS knockout mice (iNOS-/-). At 13 months of age, mice were allocated according to their genotype to one of 4 study groups: wild type (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Endothelin-1 initiation of HF is accompanied by large increases in iNOS activity, and Kalk et al ., showed that a mouse iNOS knockout was largely protected from endothelin-1 initiated HF [78]. They concluded that endothelin-1 induced cardiac injury “is at least partially mediated by iNOS”.…”
Section: Role Of Elevated No/onoo-cycle Elements In Hfmentioning
confidence: 99%
“…Endothelin-1 initiation of HF is accompanied by large increases in iNOS activity, and Kalk et al ., showed that a mouse iNOS knockout was largely protected from endothelin-1 initiated HF [78]. They concluded that endothelin-1 induced cardiac injury “is at least partially mediated by iNOS”.…”
Section: Role Of Elevated No/onoo-cycle Elements In Hfmentioning
confidence: 99%